Thermodynamic Stability Areas of Polyvanadates of Alkaline Earth Metals - Igor Povar; Inga Zinicovscaia; Oxana Spinu; Boris Pintilie (Journal of Chemistry)
A thermodynamic method of the global Gibbs energy variation calculation for describing heterogeneous equilibria of transformations of calcium, strontium, and barium polyvanadates, that occur in systems MeO-V2O5-H2O, where Me is the alkaline earth element, has been developed and used. Its quintessence consists in the thermodynamic analysis of the real conditions of various processes on the basis of their total thermodynamic characteristics. On the basis of the selected thermodynamic data for involved species, the thermodynamic stability areas of solid polyvanadates towards the solution pH and vanadium and alkaline earth metal ion concentrations in heterogeneous mixtures have been established, taking into account the complex formation reactions in multicomponent heterogeneous systems. The existing experimental data confirm the results on the thermodynamic stability of polyvanadates obtained in this paper.